2009
DOI: 10.1007/s00038-009-5407-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mental health and well-being of school-children in 15 European countries using the KIDSCREEN-10 Index

Abstract: The KIDSCREEN-10 displayed good psychometric properties. Measured differences between countries, age, gender, SES, and health complaints comply with theoretical considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
108
5
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 16 publications
18
108
5
6
Order By: Relevance
“…With respect to HRQoL, the results of this study concur in great part with those reported by other authors 21,34,[40][41][42][43] ; however, we found minimal differences in HRQoL according to social class and no differences according to maternal education level. The absence of differences according to maternal level of education found in the current study may be partly explained by differences in the study methods and instruments used.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to HRQoL, the results of this study concur in great part with those reported by other authors 21,34,[40][41][42][43] ; however, we found minimal differences in HRQoL according to social class and no differences according to maternal education level. The absence of differences according to maternal level of education found in the current study may be partly explained by differences in the study methods and instruments used.…”
Section: Discussionsupporting
confidence: 92%
“…Boys’ reports of a higher level of positive health are similar to other measurements of well-being as outcome, as is the case, for example, in Kidscreen [39] and Young HUNT II [40]. Differences between the sexes have also been frequently described when health problems are measured; girls score higher than boys in, for example, depressive symptoms and those related to other mental ill health issues [41].…”
Section: Discussionmentioning
confidence: 71%
“…Several studies that utilized the "Kidscreen 52" questionnaire found that the gender differences in HRQOL are small among children prior to adolescence, but that adolescent girls tend to report worse levels of HRQOL than their male counterparts (Bisegger et al 2005;Erhart et al 2009). Most of the explanations for the emergence of these gender differences in HRQOL in adolescence refer to biological factors (e.g., that puberty is physically harder for girls), psychological factors (e.g., that girls cope with problems internally whereas boys do so externally), and social factors (e.g., that the social demands made on girls are harder to meet than those made on boys).…”
Section: Sex Differences In Health-related Quality Of Lifementioning
confidence: 99%